Acceptance and Commitment Counseling (ACC) model to improve student self-compassion and self-regulated learning - Khulaimata Zalfa; Edi Purwanta; Anik Ghufron (Jurnal Pembangunan Pendidikan: Fondasi dan Aplikasi, 2025)
This research was conducted with the aim of finding a feasible and practical Acceptance and Commitment Counseling (ACC) model to improve student self-compassion and self-regulated learning. A research and development design was used to achieve the stated objectives. In accordance with the chosen design, the research procedures included: a preliminary study to determine the need for the model; model planning; product draft development; product validation; product revision based on validation results; limited trials; revisions based on limited trial results; large-scale trials; final product revision; and dissemination of the final results. Data collection used a feasibility and practicality questionnaire completed by experts and product users. The feasibility test used the Aiken's V formula, and the practicality test used a practicality analysis based on the scores of each indicator in the practicality questionnaire. All procedures were implemented and resulted in: 1) a feasible ACC model, which was concluded based on the feasibility of each product tested. A score of 0.82 was obtained for the ACC model book, a score of 0.93 for the practice’s guide book for counselors and a score of 0.86 for the practice’s guide book for students; 2) the practical ACC model, this was concluded based on the practicality test of the practice’s guide product on counselors and students.